2018
DOI: 10.1016/j.isci.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

HOTf-Catalyzed Alkyl-Heck-type Reaction

Abstract: SummaryThe Heck reaction, along with other cross-coupling reactions, led to a revolution in organic chemistry. In the last 50 years, metal-catalyzed, photo-induced, or base-mediated Heck and Heck-type reactions have been elegantly developed. Brønsted acid-catalyzed Heck (or Heck-type) reactions are still unknown, however. By introducing alkyl peroxides as the key intermediates, primary, secondary, and tertiary aliphatic carboxylic acids are therefore applied here in a one-pot Brønsted acid-catalyzed Heck-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In contrast, alkyl-Heck-type reactions were much more challenging and rarely explored until the last decade. Pioneered by Oshima 26 and Fu's seminal works 27 , effective strategies have been developed to facilitate this alkenylations with simple alkyl halides as electrophiles [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Notably, two elegant palladium-catalyzed cases involving alkyl C-H activation were disclosed by the groups of Yu 45 and Sanford 46 , which employed N-arylamide or pyridine as a neighboring directing group with stoichiometric amounts of external oxidant.…”
mentioning
confidence: 99%
“…In contrast, alkyl-Heck-type reactions were much more challenging and rarely explored until the last decade. Pioneered by Oshima 26 and Fu's seminal works 27 , effective strategies have been developed to facilitate this alkenylations with simple alkyl halides as electrophiles [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Notably, two elegant palladium-catalyzed cases involving alkyl C-H activation were disclosed by the groups of Yu 45 and Sanford 46 , which employed N-arylamide or pyridine as a neighboring directing group with stoichiometric amounts of external oxidant.…”
mentioning
confidence: 99%
“…We performed control experiments to probe the mechanism of the reaction. It is worth noting that this coupling reaction could also be promoted by HOTf, but the reaction rates of the conversion of styrenes into the alkylated styrenes catalyzed by 5 mol % Fe(OTf) 3 were much fast than that promoted by 20 mol % HOTf. These results suggest that a catalytic amount of HOTf generated from Fe(OTf) 3 is not responsible for the reaction rates, and thus, the iron metal is the real catalyst species (Figures S1 and S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies revealed that alkyl peroxides generated from the corresponding alkyl carboxylic acids, can in the presence of a copper, 13 iron 12 and HOTf 14 catalyst act simultaneously as alkylating reagents and internal oxidants. Actually, the alkyl diacyl peroxides in a catalytic system can be simply regarded as masked alkyl electrophiles ( Fig.…”
mentioning
confidence: 99%